Optimalisasi Potensi dan Fungsi Masjid sebagai Pusat Pemberdayaan Ekonomi Masyarakat - Muchsin, Muchsin (Green Publisher Indonesia, 2025)
Empowering the poor remains a home task, not only for the government but also requiring the participation of community components according to their respective positions to engage in efforts to empower the poor in all aspects of life. Mosques, as centers of Islamic community activities, have significant potential in enhancing the empowerment of the poor, as it is a mandate of Islamic teachings to empower them. To support efforts in finding solutions, the researcher is interested in discussing the theme of empowerment through research that employs a descriptive qualitative method by conducting direct interviews with informants to obtain primary and secondary data, and observing to understand aspects related to the internal and external conditions of the research object. The results of the interview data are documented and supplemented with SWOT analysis. This aims to assist mosques in optimizing their potential and functions to add value in serving the community and achieving optimal community empowerment.